Impact of Demobilization on Indian Economy: The Rise of the Automotive Industry and its Impact on the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The automotive industry emerged in the late part of the nineteenth century. Then technological innovation, improvements, and uncertainty ruled the day. In 1900, Ranson E. Olds sold 500 cars to prove the commercial feasibility of the product. The entrepreneur Henry Ford appreciated the huge demand for a car priced such that most Americans could afford it. Ford's price sensitive strategy paid off when Model T came out in 1908. Demand that exceeded supply His strategy of mass production and extensive dealer network resulted in a market share of more than 50 in the early 1920s.